2012
DOI: 10.3389/fneur.2012.00172
|View full text |Cite
|
Sign up to set email alerts
|

P300 and Neuropsychological Assessment in Mild Cognitive Impairment and Alzheimer Dementia

Abstract: Only a small proportion of individuals with Mild Cognitive Impairment (MCI) will convert to dementia. Methods currently available to identify risk for conversion do not combine enough sensitivity and specificity, which is even more problematic in low-educated populations. Current guidelines suggest the use of combined markers for dementia to enhance the prediction accuracy of assessment methods. The present study adhered to this proposal and investigated the sensitivity and specificity of the electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 79 publications
6
38
1
2
Order By: Relevance
“…Previous studies have suggested that elderly people with MCI have lower executive functioning compared to age-matched controls, leading to less efficient inhibitory control and working memory [21,33]. In the present study the accuracy rates and RTs in the homogeneous condition for the aMCI subjects did not differ significantly from those of the controls, a result that is in agreement with Belleville et al's [33] findings, indicating that people with aMCI have no particular problem in managing such tasks in isolation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Previous studies have suggested that elderly people with MCI have lower executive functioning compared to age-matched controls, leading to less efficient inhibitory control and working memory [21,33]. In the present study the accuracy rates and RTs in the homogeneous condition for the aMCI subjects did not differ significantly from those of the controls, a result that is in agreement with Belleville et al's [33] findings, indicating that people with aMCI have no particular problem in managing such tasks in isolation.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research reported that the P3 latency was stable and sensitive in cognitive evaluations of MCI patients and those with conversion from MCI to AD [23]. Indeed, a number of experimental studies also demonstrated prolonged P3 latency in the elderly with aMCI [21,72] and MCI [73][74][75] when performing the visual and auditory oddball tasks. Therefore, in support of these earlier findings, the prolonged P3 latency found in the current paper seems to be a neuropathological characteristic of MCI.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A rationale for investigating the P300 is its potential as a robust biomarker of cognitive dysfunction. For example, EEG research in other clinical contexts has found that P300 marks cognitive dysfunction in chronic headache 11 , chronic lower back pain 12 , phantom limb pain 13 , schizophrenia 14 , disorders of consciousness 15 and dementia 16 . The P300 is thought to reflect cognitive updating processes that are sensitive to task demands (providing a marker of attentional resource allocation).…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%